2001
DOI: 10.1007/s005200100237
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic complications related to indwelling central venous catheters in children with oncological/haematological diseases: a retrospective study of 362 catheters

Abstract: Indwelling central venous catheters (CVC) are essential devices in the management of children with oncological/haematological diseases being treated with chemotherapy or undergoing bone marrow transplantation. Our study was aimed at detecting the incidence of important thrombotic events caused by CVC in children, and the coexistence of coagulation disorders in children affected with thromboembolic disease related to CVC. Therefore, we describe some antithrombotic strategies which have been successfully applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
1
21
1
2
Order By: Relevance
“…In many centers, the total number of cases clearly increased over the last 10 years. This urgently necessitates a reevaluation of the actual incidence [5, 7, 8, 16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many centers, the total number of cases clearly increased over the last 10 years. This urgently necessitates a reevaluation of the actual incidence [5, 7, 8, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Ninety percent involve the lower half of the body [54]. Symptomatic catheter-associated thrombosis, mainly connected to an increasing number of interventions in the fields of cardiology, oncology and intensive care, are equally spread throughout all the age groups [5, 7, 8, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…If CVC was correctly positioned, a Doppler ultrasound (US) and/or 2D echocardiography were performed to look for deep vein thrombosis (DVT) or thrombi at or near the device tip [7]. Subjects with documented DVT or right atrial thrombus were excluded from this study and treated with other institutional protocols.…”
Section: Design and Methodsmentioning
confidence: 99%
“…The causes of obstruction may be mechanical, chemical (drugs or nutrients, precipitating in the lumen), or thrombotic [4,5,[11][12][13][14][15][16][17]. One of the most frequent causes of CVC dysfunction and occlusion is the formation of a fibrin sheath inside the lumen or at the apex of the catheter, especially in that case without apparent signs of compression or of dislocation, and without a history of infusions of drugs at risk of giving precipitates (i.e., TPN, etoposide, etc.).…”
Section: Definitions and Diagnosismentioning
confidence: 99%
“…Indeed, two retrospective studies have reported a significant association of CVC dysfunction and TE [9,12]. Figure 1 summarizes the various thrombotic complications of CVC and the mode of presentation.…”
Section: Definitions and Diagnosismentioning
confidence: 99%